Family Dynamics over the Life Course Foundations, Turning Points and Outcomes - Baxter, Janeen; Lam, Jack; Povey, Jenny; Lee, Rennie; Zubrick, Stephen R. (Life Course Research and Social Policies,, 2022)
This open access book examines how families and other social institutions interact to shape outcomes over the life course. It considers how to use research evidence to reduce social disadvantage through translation of evidence to support public policies and programs. The chapters focus on key life course stages such as early child development, adolescence, emerging adulthood, parenting, marriage, relationships and ageing, as well as examining experiences and outcomes for selected social groups such as Indigenous children, migrants and refugees, and gay, lesbian and bisexual groups. The book presents evidence using high-quality and recent data. With a focus on Australia, the volume provides new insights into how context shapes life course pathways and outcomes and a contrast to work that typically focuses on Europe and the United States. It will be of value to anyone interested in understanding how family background and life course pathways influence social disadvantage.